Isolation and Identification of Dermatophytes and Evaluation the Inhibitory Effect of Nanoparticles Synthesized by Pseudomonas Aeruginosa on Isolated Fungi in Al-Shirqat - Khalaf, Abdullah Ahmed; Mohammed, Bari Lateef; Abdullah, Iman Tajer (American Journal of Biology and Natural Sciences, 2025)
This study was conducted to investigate the prevalence of dermatophytes in the Al-Sharqat District and evaluate the inhibitory effects of nanoparticles synthesized by Pseudomonas aeruginosa against isolated dermatophytes. This study was performed during the period from November 2023 to June 2024. A total of 160 clinically diagnosed skin samples were collected from patients aged between 1 month to 70 years from both sexes. Direct microscopic examination using 10% KOH revealed that 103 skin samples (64.4%) were positive and 57 (35.6%) were negative. Culturing on Sabourad dextrose agar showed fungal growth in 112 samples (70%) and no growth in 48 (30%). Among the identified dermatophytes, Trichophyton strains accounted for 43 (38.4%) and Microsporum strains 7(6.2%). Trichophyton mentagrophytes was the most prevalent 24 ( %) followed by Microsporum audouinii 5 ( %). Additionally, 28 (25%) Aspergillus isolates and 34 (30.4%) Candida species were also detected. Males had a higher susceptibility to dermatophyte infections (76.8%) compared to females (23.2%), with the 21-30 age group (24.1%) being the most affected. The isolates were treated with nanoparticles synthesized by P. aeruginosa, showing significant inhibitory effects on T. mentagrophytes and Microsporum canis, with sensitivity rates of 65% and 60%, respectively, at a concentration of 4 mM.